The Prevalence of Renal Stones and Outcomes of Conservative Treatment in Kidney Transplantation: A Systematic Review and Meta-Analysis - Fakhr Yasseri, Alimohammad; Saatchi, Mohammad; Khatami, Fatemeh; Dialameh, Hossein; Rahimzadeh, Hormat; Aghamir, Seyed Mohammad Kazem (Urology Journal, 2021)
Background: Nephrolithiasis is a rare complication in transplanted kidneys and limited information is available about its therapeutic options. This study aimed to review the conservative management of urinary lithiasis and its outcomes in renal transplanted patients. Methods: A systematic review and meta-analysis of the scientific literature were performed in the Medline, Scopus, and Embase databases. Inclusion criteria were studies which include patients with kidney stones in transplanted kidney no matter de-novo or donated stones and use conservative treatment for all or part of their patients. Exclusion criteria were bladder & ureteral stones, full text unavailable, conference paper. (from January 1st, 1980, to the 19th May 2020). The results of included studies, in the final analysis, were combined using a random-effect model and using metaprop method prevalence and 95% CI of renal stone were reported. Results: A total of 8 studies (14988 transplant patients) met the inclusion criteria for the final analysis. A total of 195 patients suffered from renal stone and the prevalence of renal stone was 1.3% (95% CI: 0.89% - 1.7%). The mean age of these patients was 43 years. analysis, the prevalence of conservative treatment in 195 patients was 35% (95% CI: 19%-51%). The mean stone size ranged from 0.29 cm to 1 cm. Three studies reported a stone-free rate of %100. Except for two studies that did not report complications, other studies reported zero percent. Conclusion: More than one-third of nephrolithiasis were conservatively managed in transplanted patients. Despite limited data, conservative treatment could be done in less than 4 mm stones with high Stone Free Rate (SFR) and very low complications.